Evaluasi Penerimaan Masyarakat Terhadap Program Mobil Pusat Layanan Internet Kecamatan - Slamet Enggo Widodo; Silmi Fauziati; Hanung Adi Nugroho (Jurnal EECCIS, 2015)
Mobile District Internet Service Center (MDISC) is a mobile internet service center for secure, fast and low cost internet access in districts area. As one of the a government program, MDISC intended to facilitate areas which had relatively low access to information and internet. MDISC was a new program for the targeted society, therefore the citizens reacted differently towards it. The public accceptance becomes important to be evaluated, since it is considered as one of the succesful implementations factors. The survey was held towards 108 respondents as the MDISC users in six districts of Balangan Regency. This study applied the UTAUT method adapted by Anderson et al. with several modifications. The method was choosen due to the ability to explain the user acceptance of the information technology system from the user side. Data was analysed using SEM with SmartPLS. The result showed that the performance expectancy, the facilitating condition, and the experience influenced the use behaviour significantly. On the other side, the effort expectancy, social influence dan voluntariness of use had insignificant influences.Index Terms—Evaluation, Use Behavior, UTAUT.